PENGARUH KONTEN TREN RUNNING TERHADAP GAYA HIDUP BERLARI PADA MAHASISWA PENGGUNA AKTIF TIKTOK DI UNIVERSITAS NEGERI GORONTALO - Siti Altasya Tangahu; Sirrajudien Bialangi; Ramly Abudi (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2026)
The development of social media, particularly TikTok, has influenced the behavior and lifestyle of young people, including physical activity and sports participation. One emerging phenomenon is the increasing popularity of running trend content that presents running activities as part of a healthy lifestyle. This study aimed to analyze the influence of running trend content on the running lifestyle among active TikTok users at Gorontalo State University. This study employed a quantitative approach using a survey analytic method with a cross sectional design. The population consisted of active TikTok users at Gorontalo State University, with 100 respondents selected through purposive sampling. The research instrument used a Likert-scale questionnaire that hadbeen tested for validity and reliability. Data analysis was conducted using univariate analysis, classical assumption tests, and simple linear regression. The findings showed a significant influence of running trend content on the running lifestyle with asignificance value of 0.000 and a coefficient of determination of 33.1%. The study concludes that exposure to running trend content on TikTok can influence students’ tendency to adopt a running lifestyle as part of a healthy lifestyle.